If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(k + 6) = -2(3k + -6) Reorder the terms: 3(6 + k) = -2(3k + -6) (6 * 3 + k * 3) = -2(3k + -6) (18 + 3k) = -2(3k + -6) Reorder the terms: 18 + 3k = -2(-6 + 3k) 18 + 3k = (-6 * -2 + 3k * -2) 18 + 3k = (12 + -6k) Solving 18 + 3k = 12 + -6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '6k' to each side of the equation. 18 + 3k + 6k = 12 + -6k + 6k Combine like terms: 3k + 6k = 9k 18 + 9k = 12 + -6k + 6k Combine like terms: -6k + 6k = 0 18 + 9k = 12 + 0 18 + 9k = 12 Add '-18' to each side of the equation. 18 + -18 + 9k = 12 + -18 Combine like terms: 18 + -18 = 0 0 + 9k = 12 + -18 9k = 12 + -18 Combine like terms: 12 + -18 = -6 9k = -6 Divide each side by '9'. k = -0.6666666667 Simplifying k = -0.6666666667
| (5+8)(x-5)=0 | | A=7y+6yx | | 10-6g=-32 | | 3y-5+4y=16 | | 4(-6x+9)=324 | | 10z-z=-3+2z-3-1 | | 10(2-4n)+3a=353 | | 9x^2-63x+110=0 | | -280=-8(3-8n) | | 3a+3=36 | | 8x=12x^2-2 | | -7x+3x=-6 | | 6+9q=10+8q | | 8x-7=5x-58 | | 3y-5+4=16 | | 8a+4=6+a | | 50x-1100=-15x+3450 | | 10(-9n-4)=-850 | | (2m+1)9+5(5m+3)=0 | | -6(7x-6)=330 | | (2-9i)(9-6i)= | | -38-a=-5(1-2a) | | 40t^2+40t=1200 | | 6(x-1)+7=7(8x-7) | | 12-5x-4kx=yforx | | x-9=-16+2x | | 12+x-x^2=0 | | 2(7x-2)+7(-8-x)=-2x+5+2x+5 | | 2(5x-4)+9=7(x+1) | | 126=-6+3(-5p-6) | | 1250n+25=800 | | 3(2x+9)=-35+56 |